EFFECT OF MULTI WALLED CARBON NANOTUBES ADDITION ON THE MECHANICAL AND THERMAL PROPERTIES OF EPOXY MATRICES - Hassan, Najiba Abdullah; Al Kabi, Jamal Jasim Rady (MAGISTRA, 2015)
This study focuses on development and characterization of thermosetting resin (epoxy resin) based nanocomposites containing multi walled carbon nanotubes (MWCNTs). CNTsÂ epoxy composites have been fabricated using solution processing with different volume fraction Vf % of CNTs. Three bending test, Vickerâs hardness and thermal conductivity tests were performed on unfilled and CNTÂfilled epoxy to identify the loading on the properties of materials. Mechanical test results showed that epoxy resin and CNTs/epoxy composites behavior as ductile material ,and the results showed that the flexural properties were inferior to those exhibited by the pure epoxy matrix. While microhardness testing showed improve the hardness of composites. The thermal properties of neat epoxy resin and multi wall carbon nanotube (MWCNTs) / epoxy composites were measured by Leeâs disc technique. The experimental results show were slightly enhanced of thermal conductivity (as compared to the neat) with increasing volume fraction of CNTs. Keyword : Multi walled carbon nanotube, epoxy matrices